Everyday Life Theories of Emotions in Conflicts From Bali, the Spanish Basque Country, and the German Ruhr Area - Kurilla, Robin (Frontiers in Psychology, 2020)
This paper presents findings from a cross-cultural study on emotions in conflicts in Bali, the Spanish Basque Country, and the German Ruhr Area. The study had two aims: 1) to investigate the ways in which individuals make sense of how emotions, their expressions, and interaction conflicts are interrelated; 2) to compare the findings from the three regions. A particular interest was to explore and compare everyday life emotion theories. Ten semi-structured interviews were conducted in each region. This method was triangulated with cross-cultural narrative interpretations and the task of relating emotion words to conflicts. The data were subjected to qualitative content analysis. The results show that partly different emotions were related to conflicts in the three datasets and that similar emotions may differ in antecedents, conceptual foundation, and behavioral consequences. Emotions similar to anger were commonly related to conflicts. In Bali, this emotion was mainly expressed through silence and rather hypocognated. The respective emotions received a deeper conceptual analysis and also served as conflict models in the other regions. Emotions similar to pride were related to the prolongation of conflicts in the Basque Country, considered causes of conflicts in the Ruhr Area, but were not related to conflicts in Bali. All three datasets show that the main indicators used to ascribe emotions to others are not facial expressions but subtle nuances and omissions of typical behavior and conventionalized signs. In the Basque Country, the emotions respeto and confianza form a continuum for the codification of interpersonal distance that produces different levels of expressiveness. These emotions act as a culture-specific socio-emotional means of emotion regulation. The Balinese emotion lek has a similar function, as it neutralizes emotions similar to anger at their onset, acting as a substitute for deliberate forms of emotion regulation. All three datasets indicate that a hydraulic model is employed to conceptualize emotions although the suppression of expressions is not pathologized in Bali but considered rather difficult to achieve. The communicative imaginaries of how emotions are experienced were surprisingly similar, with the exception that in Bali emotions are situated in the liver and described with a gustatory nomenclature.